2008
DOI: 10.1007/s12011-008-8217-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exhaustion and Calcium Supplementation on Adrenocorticotropic Hormone and Cortisol Levels in Athletes

Abstract: The present study was performed to investigate the effects of strenuous exercise and calcium supplementation on cortisol and adrenocorticotropic hormone levels in athletes at rest and exhaustion. Thirty male athletes, ages 17-21 years, were enrolled in the 4-week study. They were divided into three groups as follows: group 1 (n = 10): training without supplementation; group 2 (n = 10): training and calcium supplemented, and group 3 (n = 10): calcium supplemented without training. Venous blood samples were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Cinar et al [92,93,94,95,96] investigated the influence of Ca (~37 mg·kg·day −1 ) and exhaustive exercise (90 min·day −1 , 5 days·week −1 ) on a number of exercise-related blood markers, in a series of studies in the same sample of amateur athletes ( n = 30). The authors concluded that circulating Ca, Potassium (K), Copper (Cu), Testosterone (T), Glucose, Leukocyte and Erythrocyte levels were altered following exhaustive exercise and occurred to a greater extent with exercise plus Ca supplementation [92,93,94,95,96]. However, these conclusions are misleading, as the presented results suggest that it was more likely that exhaustive exercise that influenced these changes, rather than Ca supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Cinar et al [92,93,94,95,96] investigated the influence of Ca (~37 mg·kg·day −1 ) and exhaustive exercise (90 min·day −1 , 5 days·week −1 ) on a number of exercise-related blood markers, in a series of studies in the same sample of amateur athletes ( n = 30). The authors concluded that circulating Ca, Potassium (K), Copper (Cu), Testosterone (T), Glucose, Leukocyte and Erythrocyte levels were altered following exhaustive exercise and occurred to a greater extent with exercise plus Ca supplementation [92,93,94,95,96]. However, these conclusions are misleading, as the presented results suggest that it was more likely that exhaustive exercise that influenced these changes, rather than Ca supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the MMNs included both calcium and magnesium, 2 nutrients present in LNSs but absent in the MMNs used in our study. In a trial in Gambia, lactating women who were provided a supplement containing energy, protein, riboflavin, vitamin A, vitamin C, and calcium during lactation had lower maternal cortisol than did controls (63); however, other studies that provided nonpregnant individuals with calcium or milk supplementation found no effect on cortisol (64,65).…”
Section: Discussionmentioning
confidence: 99%